Optimization of Aqueous Extraction of Virgin Coconut Oil Using Response Surface Methodology - Agarwal, Ravindra Kumar; Bosco, S. John Don (International Coconut Community, 2013)
The present investigation deals with optimization of aqueous extraction process for maximum yield of virgin coconut oil (VCO) from coconut milk extracted from coconut meat. Optimization of the process parameters including dilution ratio (w/w), grinding time (min), temperature (°C), cream separation time (hour) and pH was analyzed using one-factor-at-a-time (OFAT) method and response surface methodology based central composite design methods. OFAT method revealed the dilution ratio of 1:1 and grinding time of 3 min to enhance the yield of VCO whereas central composite design optimized the temperature at 33°C, cream separation time for 4 hours and pH of coconut milk at 6.5 for the maximum VCO yield of 20.38/100g of fresh coconut meat contained 32.82g/100g fat (w/w). Hence the percentage oil recovery of VCO was found to be 83.12 per cent (w/w) of fat present in fresh coconut meat. The analysis of variance (ANOVA) of central composite design revealed that temperature (P<0.05), pH (P<0.05) and interaction of these two parameters were highly significant for the yield of VCO with the second order model having the co-efficient of determination (R2) of 0.97.